Business Finance and Banking in Nigeria - Osubor, John Uche. (Owerri, Imo State, Nigeria : New Africa Pub. Co., 1984)
The book which has sixteen chapters falls into two parts. The first part deals with the surroundings of business while the second part deals with financing and management of business firms.
Bibliography: p. 207-209.
osc 10/5/17
Loans
Keywords: Banks and banking; Financial institutions; Business enterprises; Corporations